2004
DOI: 10.1038/sj.bjc.6601679
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of MLH1 and CDKN2A in oncogenesis of laryngeal cancer

Abstract: Our study aimed at elucidating which genetic alterations tend to form a network and could be applied as molecular markers of larynx squamous cell carcinoma (LSCC). A panel of genes involved in tumorigenesis was investigated. To search for the possible mechanisms of gene silencing, loss of heterozygosity (LOH) was analysed followed by testing DNA methylation and protein expression for those genes found with the highest frequency of LOH (CDKN2A (55.4%), MLH1 (46.0%), RB1 (35.7%)). A correlation of both LOH and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
2
22
0
1
Order By: Relevance
“…Consistent with previous observation in head and neck cancer, it was found that 7 (10.4%) of the 67 informative cases had LOH of the Rb gene [11][12][13]. In our study low frequency of loss for Rb confirms the results obtained by Lee in head and neck cancer (15%) and Kannan in oral cancer (17%) [11,13].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consistent with previous observation in head and neck cancer, it was found that 7 (10.4%) of the 67 informative cases had LOH of the Rb gene [11][12][13]. In our study low frequency of loss for Rb confirms the results obtained by Lee in head and neck cancer (15%) and Kannan in oral cancer (17%) [11,13].…”
Section: Discussionsupporting
confidence: 82%
“…Loss of heterozygosity at the retinoblastoma gene in the mentioned study of laryngeal supraglottic cancer [1) occurred at a frequency (59%) close to that found in non small cell cancer (48%) [14] or oesophageal cancer (54%) [10]. Nevertheless, for head and neck cancer LOH for Rb is rather infrequent [11][12][13]. Although, the reason for this high percentage of LOH for Rb in those studies might be connected with the chosen investigated group related only to supraglottic laryngeal cancer cases.…”
Section: Discussionmentioning
confidence: 99%
“…The modern automatic fragment analysis procedures offer high throughput analysis and a more precise and quantitative 60 -64 Although other points of discussion are the cutoff values to be used for LOH ratios (the ratio between the peak height ratios of both alleles of normal and paired tumor sample), 9,39,63,65 there is fairly general agreement that appropriate cutoffs are 42 or o0.5. A last issue is on the different types of MSI.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…17,18,19,33 There are several reports that LOH is associated with more advanced stage and more aggressive HNSCC tumors, 13,34,36,37,56 and specifically with nodal involvement. 32,44 Other authors describe very specific correlations such as a link between LOH at 17p and mitotic index, 39 a connection of LOH at MLH1 with lower grade HNSCC, and LOH at CDKN2A with higher grade, 9 or a preference of LOH in tumors originating from the pharynx. 56 A correlation between LOH and other patient-related factors like age and race, was described in some studies.…”
Section: Lohmentioning
confidence: 99%
See 1 more Smart Citation